The Effect of Postural Correction and Exercise on Neck Pains in Cell Phone Users - Ozan Soyer; Zeynep Ülkü Akarırmak (Galenos Yayinevi, 2020)
Objective:Using a cell phone in the head forward posture for a long time is a risk factor for the induction of trigger points (TP) and myofascial pain syndromes (MPS). The purpose of this study was to evaluate the association between cell phone use-related neck pain and MPS in the trapezius, sternocleidomastoideus and levator scapulae (LS) muscles as well as to determine an appropriate treatment approach.Materials and Methods:In total, 49 patients who had neck pain and reported using a cell phone were included in this study and divided randomly into two groups. Taut band existence and TP pain severity were evaluated in the trapezius, sternocleidomastoideus and LS muscles. In addition, neck pain severity and range of motion (ROM) were assessed. Group 1 received a structured exercise programme and posture correction advice, whereas group 2 did not receive any treatment. The patients were re-evaluated again after 1 month, and these parameters were compared with those at the first examination.Results:A total of 47 patients completed this study. In group 1, the neck pain score was found to be significantly decreased (p<0.001), and the taut band of the right LS muscle to have significantly disappeared (p=0.004). A significant decrease in TP pain severity was found on the 2nd point of the left sternocleidomastoideus (p=0.039), left trapezius (p=0.031), and right LS (p=0.012) muscles. In addition, a borderline decrease in pain was found in the 2nd point of the left LS muscle in group 1, although it did not reach statistical significance (p=0.056). On the other hand, there were no significant changes in terms of neck pain score, taut band existence and TPs pain severity in group 2. Pain and limitation of ROM showed no significant difference between the first and second examinations in both groups.Conclusion:Limiting the duration of mobile phone usage, performing regular exercises and correcting the head forward position by increasing awareness can be helpful in preventing the development of text neck syndrome.